Haemosporidian parasites and incubation period influence plumage coloration in tanagers (Passeriformes: Thraupidae). Issue 1987 (30th November 2022) - Aguiar de Souza Penha, Victor; Maia Chaves Bicalho Domingos, Fabricius; Fecchio, Alan; Bell, Jeffrey A.; Weckstein, Jason D.; Ricklefs, Robert E.; Braga, Erika Martins; de Abreu Moreira, Patrícia; Soares, Letícia; Latta, Steven; Tolesano-Pascoli, Graziela; Alquezar, Renata Duarte; et al.
Abstract : Birds are highly visually oriented and use plumage coloration as an important signalling trait in social communication. Hence, males and females may have different patterns of plumage coloration, a phenomenon known as sexual dichromatism. Because males tend to have more complex plumages, sexual dichromatism is usually attributed to female choice. However, plumage coloration is partly condition-dependent; therefore, other selective pressures affecting individuals' success may also drive the evolution of this trait. Here, we used tanagers as model organisms to study the relationships between dichromatism and plumage coloration complexity in tanagers with parasitism by haemosporidians, investment in reproduction and life-history traits. We screened blood samples from 2849 individual birds belonging to 52 tanager species to detect haemosporidian parasites. We used publicly available data for plumage coloration, bird phylogeny and life-history traits to run phylogenetic generalized least-square models of plumage dichromatism and complexity in male and female tanagers. We found that plumage dichromatism was more pronounced in bird species with a higher prevalence of haemosporidian parasites. Lastly, high plumage coloration complexity in female tanagers was associated with a longer incubation period. Our results indicate an association between haemosporidian parasites and plumage coloration suggesting that parasites impact mechanisms of sexual selection, increasing differences between the sexes, and social (non-sexual) selection, driving females to develop more complex coloration.